MtDNA ND2 sequence identifies Streaked Horned Lark (Eremophila alpestris strigata) from birdstrike to US Air Force F-15 at Portland International Airport, Oregon - Dove, Carla J.; Dahlan, Nor Faridah; Drovetski, Sergei V. (Conservation Genetics Resources, 2013)
The Streaked Horned Lark (SHL: Eremophila alpestris strigata) is the Northwest subspecies of the Horned Lark listed as endangered in Washington State, critical in Oregon, and is now being considered for listing as threatened by the US Fish & Wildlife Service. Some of the important breeding areas of SHL are associated with airports in western Washington and Oregon which raises concern over possible collisions between SHLs and aircraft. Here, we report a successful use of mtDNA ND2 gene sequence for identification of SHL feather and tissue remains from a bird collision with a US Air Force F-15-C on 4 October 2012 at Portland International Airport. Due to the conservation status of SHL, documentation of this event and a simple mtDNA-based molecular identification protocol may have management and conservation implications at airfields within the range of this rare subspecies.